An Epidemic Model of Investor Behavior - Shive, Sophie (Journal of Financial and Quantitative Analysis, 2010)
Abstract I test whether social influence affects individual investors’ trading and stock returns. In each of the 20 most active stocks in Finland over 9 years, the number of owners in a municipality multiplied by the number of investors who do not own a stock, a measure of the rate of transmission of diseases and rumors through social contact, predicts individual investor trading. I control for known determinants of trade, including daily news, and show that competing explanations for the relation are unlikely. Socially motivated trades predict stock returns, and the effects are not reversed, suggesting that individuals share useful information. Individuals’ susceptibility to social influence has declined during the period, but the opportunities for social influence have increased.